PENGARUH KONSERVATISME AKUNTANSI TERHADAP PENILAIAN EKUITAS PERUSAHAAN DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL PEMODERASI (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2015 – 2017) - Mukminah Mukminah; Maslichah Maslichah; Muhammad Cholid Mawardi (Universitas Islam Malang, 2018)
ABSTRACTThis study was conducted to determine the effect of accountingconservatism on the assessment of corporate equity with good corporategovernance as a moderating variable. The study was conducted at amanufacturing company listed on the Indonesia Stock Exchange (BEI).Determination of sample in this research using purposive sampling method. Thetotal sample is 32 companies. Data were analyzed using moderate regressionanalysis (MRA) analysis.The result of research shows that accountancy conservatism hassignificant effect to company's equity valuation, where moderate variable ofmanagerial ownership and number of board of commissioner have no significanteffect. In this research also use Moderate Regression Analysis (MRA) todetermine moderation type in moderation variable, while managerial ownershipand number of board of commissioner is not a kindofquasi moderationvariable.Keywords:Accounting Conservatism, Corporate Equity Assessment, GoodCorporate Governance